1996
DOI: 10.1046/j.1365-2567.1996.d01-736.x
|View full text |Cite
|
Sign up to set email alerts
|

Alloproliferation of purified CD4+ T cells to adult human heart endothelial cells, and study of second‐signal requirements

Abstract: SUMMARYHuman endothelial cells have been shown to be capable of causing direct allostimulation of T cells. However, the majority of immunological studies of human endothelial cells have been performed on cells of fetal origin. Here we use endothelial cells isolated from the adult human heart, both large vessel (coronary artery, pulmonary artery and aorta) and also microvascular. We have examined the ability of all these endothelial cells to cause direct allostimulation of T cells, and show that purified CD4T c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 30 publications
2
19
0
Order By: Relevance
“…HLA-DM and Ii were also up-regulated on both cell lines. It was then shown that CIITA transfection did not alter cell surface expression of LFA-3, known to be a second signal for endothelial cell-mediated stimulation of CD4 ϩ T cells (17,28,34). Expression of ICAM-1, CD40, and HLA class I also remained unaltered after CIITA transfection.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…HLA-DM and Ii were also up-regulated on both cell lines. It was then shown that CIITA transfection did not alter cell surface expression of LFA-3, known to be a second signal for endothelial cell-mediated stimulation of CD4 ϩ T cells (17,28,34). Expression of ICAM-1, CD40, and HLA class I also remained unaltered after CIITA transfection.…”
Section: Discussionmentioning
confidence: 98%
“…There is a broad agreement that HLA class II-positive endothelial cells (5,6,16,28,29), but not epithelial cells (7,(11)(12)(13)(14)30), fibroblasts (31,32), or smooth muscle cells (28,33), cause alloproliferation of resting CD4 ϩ T cells. The advantage of CIITA transfection is that it can cause up-regulation of HLA-class II molecules without the pleiotropic effects of IFN-␥.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas CD80 and CD86, which provide the major costimulation for unprimed T cell responses, are lacking on RMEC, CD58, which has been associated with HLA-DR-initiated T cell activation in allogeneic assays with cardiac microvascular endothelial cells (39), is abundant on RMEC. CD40 is not normally expressed on RMEC in vivo, but a low level of CD40 is consistently induced by unknown factors in our cultured RMEC.…”
Section: Discussionmentioning
confidence: 99%
“…ϩ T cells after coculture with cytokine-activated human endothelial cells, others have reported the inability of cytokine-activated endothelium to initiate CD4 ϩ alloresponses (8,(25)(26)(27). Similar to human endothelium, MHC class II is induced after treatment with IFN-␥ on cultured mouse vascular endothelium (12,13).…”
Section: Discussionmentioning
confidence: 99%